Design of an information-measuring system for monitoring deformation and displacement of rock massif layers based on fiber-optic sensors - Yugay, Vyacheslav; Mekhtiyev, Ali; Neshina, Yelena; Aubakirova, Bakhytkul; Aimagambetova, Raushan; Kozhas, Aigul; Alkina, Aliya; Musagazhinov, Madiyar; Kovtun, Alexandr (Eastern-European Journal of Enterprise Technologies, 2021)
This paper reports a study into designing an information-measuring system that could be used in coal mines that are dangerous in terms of the explosion of coal dust and methane gas. The results of reviewing technical advancements in the field of fiber-optic system development are given. To solve the set task, prototypes of a fiber-optic sensor of a new type and a hardware-software complex were constructed. The research aims to improve the safety of workers at coal enterprises. The result of the theoretical research has established that additional losses related to a micro bending should be taken into consideration while accounting for the effect of photoelasticity. The fundamental difference between the idea reported here and existing analogs is the development of a hardware-software complex capable of working with a single-mode optical fiber of great length with a significant noise level. The data processing unit is equipped with a television matrix and can analyze changes in the pixels of a light spot. The proposed system is quasi-distributed; it controls individual points within a rock massif. The designed hardware-software system provides high noise immunity of measuring channels when the external temperature changes. The research results helped develop an information-measuring system for monitoring the deformation and displacement of rock massif layers based on fiber-optic sensors, capable of operating in an explosive environment. The system makes it possible to control several layers located in the roof of the workings, while the fiber-optic sensor may contain two or three sensitive elements that are connected to different channels. With a sharp fluctuation in pressure and an increase in the displacement parameter, the system triggers a warning signal about the danger.